The Emotional Consequences of Organizational Change - Grenier, Amanda; Bidgoli, Elham (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2015)
This paper explores the emotional experiences of professionals in a health and social care setting during a process of reform in the Canadian province of Quebec. Characterized as “new public management” or “new managerialism,” public health and social care services in a number of countries have undergone reforms since the early 1980s that focus on efficiency and cost reduction (Nadeau, 1996; Hornblow, 1997; Gross, Rosen, & Chinitz, 1998, Anell, 2005; Levine, 2007; Wimbush, Young, & Robertson, 2007). Although differences exist between the cultural and political contexts within which reforms are implemented, reforms regularly involve changing institutional and organizational structures, the implementation of standard procedures, and the generation of outcome measures for service. The process of reform, and the body of knowledge on organizational change however, tend to overlook the flux of emotions that take place in the everyday lives of professionals. This paper reflects on data from 25 individual interviews collected from a critical ethnography of one health and social care setting during a period of provincial health-care reform in Quebec, Canada (2004-2012). The paper provides an in-depth focus on the emotional consequences of reform as an attempt to understand and expose the human costs of change. Three patterns that professionals used to adapt to change and conflict are discussed: internalization of the reform mandate; rationalization; and creating distance between the reform and their professional or personal selves. Important in their own right, the emotions produced in a period of change provide lessons on the general stressors that surround reform, and demonstrate how health and social care professionals are often caught between policy intentions, professional values, and their personal ambitions.